Lead Levels in a Potters Population and Its Association With the Use of Different Glazes: Cross-Sectional Evaluation of the Approved Pottery Program - Peralta, Netzy; Cantoral, Alejandra; Téllez-Rojo, Martha María; Trejo-Valdivia, Belem; Estrada-Sánchez, Daniel; Richardson-L, Vesta; Caravanos, Jack; Fuller, Richard (Frontiers in Toxicology, 2022)
Lead is one of the most harmful toxic metals to humans. In Mexico, though most potters still use a lead-based glazing process, a new lead-free glaze has been introduced to the production of pottery. The Approved Pottery Program (APP) promotes the production of lead-free pottery. We aimed to document in this pilot study the blood lead levels (BLLs) of a sample of potters and the association with the type of glaze used. A cross-sectional study was conducted based on information from 46 potters grouped by 26 workshops. We measured general sociodemographic characteristics, capillary BLLs, and the lead levels of the dirt floors of the workshops. The evaluation of associations and comparisons between glaze types was performed based on a regression model clustered by workshop. Median BLL measured was 13.6 g/dL (IQR: 7.8–20.4 ug/dL), and 70% of the BLLs were greater than 10 ug/dL. Workshop managers presented higher BLLs compared to others working in the same workshop (median of 14.1 g/dL (IQR: 11.6–25.3 ug/dL) versus 10.1 ug/dL (IQR: 5.2–16.7 ug/dL), respectively). The median BLLs of potters who used lead-free glaze in at least 80% of production were 8.8 ug/dL (95% CI: -17.3 to -0.3 ug/dL) lower than the BLLs of those who used lead-free glaze in less than 30% of production, adjusted by workshop role. Lead levels were significantly lower in workshop dirt floors where lead-free glaze was used in at least 80% of the production compared to those that use less than 30% (180 versus 916 mg/kg; p < 0.05).